Las asociaciones público privadas (APP) en el marco jurídico ecuatoriano (Tema Central) - Baldeón Barriga, Inés María (2016)
In this research I analyze the Public Private Partnerships (PPP) in Ecuador from the enactment of the Ley Orgánica de Incentivos para las Asociaciones Público Privadas y la Inversión Extranjera (LOIAPP) and its General Regulations. The research was divided into 4 chapters, in which I pointed general aspects, main characteristics, legal framework and principles of PPPs at the national level and in comparative law. Also includes an analysis of possible public projects to be developed and proposed incentives. The article concludes by expressing concerns about a possible lack of legal certainty and security not only because at the moment in Ecuador doesn’t exist an APP Law, and the actual General Regulation generate more doubts than certainties, but, there is a legal framework that promotes a “Entrepreneurial State” with a residual private participation, which could make unviable the PPP projects, because of the higher cost of money.